LABORATORY PARAMETERS AND THEIR RELATIONS WITH DISEASE OUTCOME IN PATIENTS WITH NON-HODGKIN FOLLICULAR LYMPHOMA – SINGLE CENTRE FIVE-YEAR FOLLOW-UP - Jovanović, Danijela; Sretenović, Snežana; Aleksić, Sanja; Dragović, Ana; Andrejević, Ivana (Srpski medicinski časopis Lekarske komore, 2026)
Introduction/Objective: Follicular lymphoma, a subtype of non-Hodgkin lymphoma, is the second most common non-Hodgkin lymphoma and the most frequent indolent lymphoma. Although rare, this disease may exhibit aggressive behavior, a tendency toward complications, as well as resistance to administered therapy and frequent relapses. This study aimed to analyze laboratory parameters at the time of diagnosis and their association with disease outcome, complications, treatment response, and survival. Material and methods: A total of 47 patients diagnosed with follicular lymphoma between 2018 and January 2024 were analyzed at our center. Baseline laboratory parameters included complete blood count, hemostasis parameters (PT, aPTT, fibrinogen, D-dimer), and biochemical parameters. During the course of the disease, treatment response to first-line therapy, progression-free survival, and overall survival were evaluated. Results: Complete blood count parameters, as well as most biochemical parameters, showed no correlation with disease course. Complete remission was achieved in patients with lower LDH levels (p = 0.029), while overall survival was longer in patients with lower fibrinogen levels (p = 0.019), a higher percentage of monocytes (p = 0.007), and lower D-dimer levels (p = 0.000). Progression-free survival was associated with lower fibrinogen levels (p = 0.019), lower D-dimer levels (p = 0.031), lower LDH levels (p = 0.019), and a higher percentage of peripheral blood monocytes (p = 0.005). Patients with initially elevated D-dimer levels had a PFS of 24.50 ± 4.81 months, whereas those with D-dimer levels within the reference range had a PFS of 36.48 ± 5.99 months (p = 0.015). Conclusion: In our center’s experience, hemostasis parameters, particularly fibrinogen and D-dimer, showed a significant correlation with disease course.